The neurological outcome in the patients with myasthenia gravis who underwent thymectomy via sternotomy and video-assisted thoracoscopic surgery (VATS) - Martić, Vesna; Marić, Nebojša; Cvijanović, Vlado (Vojnosanitetski pregled, 2021)
Background/Aim. Thymectomy is accepted in the surgical treatment of the patients with myasthenia gravis (MG). Earlier thymectomy via sternotomy has recently been replaced by video-assisted thoracoscopic surgery (VATS), which is less invasive. The aim of this study was to determine the effectiveness and reliability of the two methods of surgical removal of the thymus by comparing the neurological outcome in patients with MG. Methods. The study included 60 patients with MG who underwent thymectomy at the beginning of their treatment: 30 patients underwent thymectomy via sternotomy, and the remaining 30 patients via VATS. In order to evaluate the effects of these two operation techniques, we compared the data related directly to the operation – the number of postoperative hospital days, the incidence of postoperative complications, as well as the data related to the neurological monitoring of these patients: directly after the operation, one year after the surgery and up to three years after the surgery. Results. The data related to the immediate postoperative period indicate a significantly shorter hospitalization after the VATS thymectomy (p < 0.001), but the percentage of postoperative complications in both groups was the same (p = 0.381). Clinical deterioration in the first year after the operation showed a uniform distribution, regardless of the type of performed operation (p = 0.470). The number of performed rethymectomies in the group that underwent thymectomy via sternotomy vs. VATS was of borderline statistical significance (p = 0.054). Complete stable remission, as a confirmation that the thymic tissue was removed in its entirety, was observed in about 11% of the patients who underwent thymectomy. For other patients, clinical remission was maintained with anticholinesterase and immunosuppressive therapy. Conclusion. The shorter hospitalization time and faster postoperative recovery, with an equal clinical efficacy and aesthetic component, favors the VATS thymectomy compared to thymectomy via sternotomy as more acceptable in the surgical treatment of the patients with MG.
Keywords: myasthenia gravis; thymectomy; sternotomy; surgery, thoracic, video-assisted; surgery, thoracic, procedures; treatment, outcome